Neuromuscular Ultrasound and Electrophysiologic Correlation of Median Mononeuropathy at the Wrist in Symptomatic Hereditary Transthyretin Amyloidosis - Kira S. Kopacz; Marcus V. Pinto; Andrea J. Boon; Marianne T. Luetmer; Ruple S. Laughlin; Brendan Putko; William J. Litchy; Michelle L. Mauermann; James B. Meiling (Journal of Clinical Neurophysiology, 2026)
Purpose: Hereditary transthyretin amyloidosis (ATTRv) is a progressive multisystem disease in which median mononeuropathy at the wrist (MNW) is common and often precedes systemic involvement. Nerve conduction studies (NCS) have historically been the gold standard for MNW, but neuromuscular ultrasound (NMUS) is complementary. The aim of this study was to compare NMUS with electrodiagnostic (EDX) testing for the diagnosis of MNW in patients with symptomatic ATTRv. Methods: A retrospective review was performed of patients 18 years and older with ATTRv confirmed by genetic testing who underwent both EDX testing and NMUS of the median nerve between 2019 and 2025. Demographic, NMUS, and EDX data were collected. Results: Data from 15 upper limbs in 10 patients were analyzed. Median nerve cross‐sectional area at the wrist was significantly greater than reference values ( P = 0.041). MNW was identified in 80% of wrists by NMUS and 100% by NCS, with no significant difference between modalities. Median nerve cross‐sectional area at the wrist did not significantly correlate with MNW severity determined by NCS ( r = −0.018; P = 0.941) or with any NCS parameters (all P > 0.080). Concurrent polyneuropathy was diagnosed in 60% of patients, but there was no association between polyneuropathy and MNW detection by either modality ( P > 0.197). Conclusions: NMUS and NCS demonstrate comparable diagnostic accuracy for MNW in ATTRv. Given its noninvasive nature and efficiency, NMUS may serve as an adjunct to classic EDX testing in this population.